Mechanical, adhesive and thermodynamic properties of hollow nanoparticles - Schwarz, Ulrich S.; Safran, Samuel; Shigeyuki Komura (Arxiv, 2002)
When sheets of layered material like C, WS$_2$ or BN are restricted to finite sizes, they generally form single- and multi-walled hollow nanoparticles in order to avoid dangling bonds. Using continuum approaches to model elastic deformation and van der Waals interactions of spherical nanoparticles, we predict the variation of mechanical stability, adhesive properties and phase behavior with radius $R$ and thickness
Gesehen am 18.12.2017